ASSESSMENT OF PURE LOSS OF STABILITY FOR A TURKISH NAVY TANKER - Muhammet Ali YILMAZER (National Defense University Barbaros Naval Sciences and Engineering Institute Journal of Naval Science and Engineering, 2021)
The second generation intact stability criteria (SGISC) have been developed by the International Maritime Organization’s (IMO) Subcommittee on Ship Design and Construction (SDC). The SGISC involve improving the current intact stability criteria by including dynamic movements of ships in waves. The criteria are structured around five failure modes, pure loss of stability being one of these. This paper presents sample calculations regarding the assessment of pure loss of stability for a Turkish navy tanker. The calculations involve two steps that this study explains: Level 1 and Level 2. In addition, Option A and Option B are used as solution methods for both levels. Minimum metacentric heights (GMmin) are calculated at the lowest draft (Option A) and at different wave crest locations alongside the ship (Option B) for Level 1. Values for the angle of vanishing stability, angle of loll, angle of stable equilibrium and maximum righting lever have been calculated from the GZ curves for Level 2. As a result, the subject ship was found not to be vulnerable to pure loss of stability. Level 1 results for both options are inconsistent due to Level 2 results being consistent.